Tham khảo bài:
\(\dfrac{1}{x}+\dfrac{y}{3}=\dfrac{5}{6}\)
\(\dfrac{1}{x}=\dfrac{5}{6}-\dfrac{2y}{6}\)
\(\dfrac{1}{x}=\dfrac{5-2y}{6}\)
\(\Rightarrow x.\left(5-2y\right)=1.6\)
\(\Rightarrow x.\left(5-2y\right)=6\)
Vì \(x.\left(5-2y\right)=6\) nên
\(\Rightarrow x.5-2y=Ư\left(6\right)=\left\{1,2,3,4,5,6\right\}\)
Vì \(5-2y\) là 1 số lẻ nên:
\(\Rightarrow5-2y=\left\{1,3\right\}\)
Lập bảng nhận xét:
x | -6 | 6 | -2 | 2 |
5 - 2y | -1 | 1 | -3 | 3 |
y | 3 | 2 | 4 | 1 |
Vậy x, y \(\in\left\{\left(-6,3\right);\left(6,2\right);\left(-2,4\right);\left(2,1\right)\right\}.\)